Optimización integral del proceso de registro de clientes y gestión de reportes de entrega en hermanos Courier. - Alban Burbano, Washington Andrés (2024)
The present study aims to optimize operational efficiency in customer registration and delivery report management at HermanosCourier through the design and implementation of the ODOO system. The company faced significant challenges in organizing deliveries and tracking packages, impacting customer satisfaction and operational efficiency. To address this issue, research was conducted, including analysis of factors affecting operational efficiency, the design of the ODOO system according to these factors, and identification of its advantages. The methodology employed focused on descriptive documentary and field research, using surveys to collect customer data. The results revealed a clear need to improve delivery management and package tracking. The implementation of the ODOO system proved to be an effective solution, providing greater organization and transparency in the company's processes. Significant progress was achieved in operational efficiency and customer satisfaction. The comprehensive optimization of the customer registration process and delivery report management through the ODOO system has proven to be an effective strategy to enhance the quality of HermanosCourier's services and strengthen its competitiveness in the logistics market.